Plasma Non Thermal Sebagai Sterilisasi Masker untuk Inaktivasi Virus Corona (COVID-19) - Fadil Abdullah; Valentinus Galih Vidia Putra (Jurnal Teori dan Aplikasi Fisika, 2022)
We used non-thermal plasma generators to sterilize textile materials, especially in personal protective equipment for masks, to inactivate viruses and bacteria attached to the mask material in this study. The design of the ozone generator utilizes the non-thermal plasma method of corona discharge using a high voltage generator with an output voltage of 3.,000 V. The sterilization process was carried out with variations in sterilization time (10,15 and 20 minutes) and an active electrode height of 3 cm. This research was carried out using CT RT-PCR testing to determine the cycle threshold value contained in the nucleic acid RNA of the COVID-19 virus before and after sterilization. Changes in CT values obtained after sterilization for 20 cycle threshold (CT) values were 37.07 for the N gene and 35,67 for the ORF. Based on the sterilization test results, no data stated that the virus was harmful. Based on these results, the increase in CT numbers is directly proportional to the length of time for sterilization so that the RNA content of the COVID-19 virus decreases. To determine the effect of the sterilization process on the hydrophilic properties of the maks, the Fourier Transform Infra-Red (FTIR) test was carried out. The study results show that non-thermal plasma can sterilize masks from the coronavirus. This study concludes that the plasma method can be used to sterilize masks from the coronavirus